2020
DOI: 10.1002/joa3.12325
|View full text |Cite
|
Sign up to set email alerts
|

Brain fog in postural tachycardia syndrome: An objective cerebral blood flow and neurocognitive analysis

Abstract: Background: It remains unclear whether brain fog is related to impaired cerebral blood flow (CBF) in postural tachycardia syndrome (POTS) patients. Methods:We assessed CBF in the posterior cerebral artery (PCA) using transcranial Doppler with visual stimuli in 11 POTS and 8 healthy subjects in the seated position, followed by neurocognitive testing.Results: CBF parameters were similar between the two groups. POTS patients demonstrated significantly longer latency in delayed match to sample response time and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…This is evidenced by the increase in omissions made by patients during head-up tilt compared to when they were supine, indicating a decrease in working memory performance. Consistent with previous findings, only cognitive performance in the head-up tilt position was impaired compared to a healthy control group, thus confirming that cognitive dysfunction in POTS is a functional, and not an absolute deficit (Ocon et al, 2012;Stewart et al, 2015;Rodriguez et al, 2019;Wells et al, 2020). The exploratory correlation analyses showed that cognitive performance during head-up tilt correlated with symptom ratings.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is evidenced by the increase in omissions made by patients during head-up tilt compared to when they were supine, indicating a decrease in working memory performance. Consistent with previous findings, only cognitive performance in the head-up tilt position was impaired compared to a healthy control group, thus confirming that cognitive dysfunction in POTS is a functional, and not an absolute deficit (Ocon et al, 2012;Stewart et al, 2015;Rodriguez et al, 2019;Wells et al, 2020). The exploratory correlation analyses showed that cognitive performance during head-up tilt correlated with symptom ratings.…”
Section: Discussionsupporting
confidence: 89%
“…A common and strongly disturbing symptom for patients is difficulty concentrating (Deb et al, 2015;Shaw et al, 2019). Patients often have problems to accurately describe their cognitive difficulties, and usually refer to them as "brain fog" or "mental clouding" (Ross et al, 2013;Wells et al, 2020). Ross et al conducted an online questionnaire-based study investigating the symptom of brain fog, and found that the most commonly used descriptors of brain fog were "forgetful, " "cloudy, " and "difficulty focusing, thinking and communicating" (Ross et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginkgo biloba extract also contains terpene lactones, which reduce blood viscosity and increase blood fl ow, resulting in improved cerebral blood fl ow [27]. It is predicted that brain fog will be partially improved by removing reactive oxygen species and improving cerebral blood fl ow in this way [26,28]. In addition to brain fog, cerebral blood fl ow decreases as blood vessels harden with age, which may lead to cognitive decline [29].…”
Section: Ginkgo Biloba Extractmentioning
confidence: 99%
“…As a comparison, the authors remarked that this deficit was larger than the mean deficit of 512 people who indicated they had previously suffered a stroke and 1016 who reported learning disabilities [ 101 ]. “Brain fog”, i.e., confusion, forgetfulness, inability to focus, fatigue, and low mental energy [ 102 , 103 ] may be thus an emerging major sequela of COVID-19 infection ( Figure 1 ).…”
Section: Melatonin and Neuroprotectionmentioning
confidence: 99%